Prophylactic antithrombotic management in adult and pediatric kidney transplantation: A systematic review and meta‐analysis. (7th April 2021) - Bapistella, Sascha; Zirngibl, Matthias; Buder, Kathrin; Toulany, Nikan; Laube, Guido F.; Weitz, Marcus
Abstract: Background: RGT is a major cause for early graft loss after KTx. Although evidence‐based recommendations are lacking, aP is often used to prevent RGT. This systematic review aimed to determine the effectiveness and safety of aP in adult and pediatric KTx recipients. Methods: MEDLINE, EMBASE, Cochrane Controlled Trials Register, conference proceedings, and electronic databases for trial registries were searched for eligible studies using search terms relevant to this review (April 21, 2020). The systematic review was carried out following the recommendations of the Cochrane Collaboration and the Prefered Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) Statement. Results: Twelve studies comprising 2370 patients (adult = 1415, pediatric = 955) were included, of which three were RCTs. The overall risk for developing RGT was lower in the group with aP compared with the control group (RR 0.24, 95% confidence interval 0.12–0.49). The antithrombotic drugs used were heparin (7/12), acetylsalicylic acid (2/12), a combination of both (2/12), and dipyridamole (1/12) with a high variability in timing, dosing, and mode of application. Adverse effects were reported rarely, with minor bleeding as the main complication. The non‐randomized studies had significant risks of bias in the domains of patient selection, confounder, and measurement of outcomes. Conclusion: Based on pooled analysis, aP seems to reduce the risk of RGT in KTx. However, the reliability of these results is limited, as the quality of the available studies is poor and information on adverse effects associated with aP is scarce. Additional high‐quality research is urgently needed to provide sufficient data supporting the use of aP in KTx.